Peptidoglycan Recognition Protein 3 Does Not Alter the Outcome of Pneumococcal Pneumonia in Mice - Shrivastav, Anshu; Dabrowski, Alexander N.; Conrad, Claudia; Baal, Nelli; Hackstein, Holger; Plog, Stephanie; Dietert, Kristina; Gruber, Achim D.; N’Guessan, Philippe D.; Aly, Sahar; Suttorp, Norbert; Zahlten, Janine (Frontiers in Microbiology, 2018)
Pneumococci frequently cause community-acquired pneumonia, a disease with high mortality rates, particularly in young children and in the elderly. Endogenous antimicrobial peptides and proteins such as PGLYRP3 may contribute to the progression and outcome of this disease. Since increasing antibiotic resistant strains occur all over the world, these endogenous antimicrobial molecules are interesting new targets for future therapies. In this study the expression pattern of PGLYRP3 was analyzed in alveolar epithelial cells, alveolar macrophages and neutrophils. Additionally, the function of PGLYRP3 during Streptococcus pneumoniae-induced pneumonia was investigated in a murine pneumococcal pneumonia model using PGLYRP3KO mice. PGLYRP3 is expressed in all selected cell types but pneumococcus-dependent induction of PGLYRP3 was observed only in neutrophils and alveolar macrophages. Interestingly, there were no significant differences in the bacterial loads within the lungs, the blood or the spleens, in the cytokine response, the composition of immune cells and the histopathology between wild type and PGLYRP3KO mice. Finally, we could neither observe significant differences in the clinical symptoms nor in the overall survival. Collectively, PGLYRP3 seems to be dispensable for the antibacterial defense during pneumococcal pneumonia.